Pengaruh Instagram Konten Marketing terhadap Purchase Intention Membership Fitness Center yang Dimediasi Brand Engagement - Septiarini, Eka; Ezra Karamang (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Utilization of content marketing through social media Instagram as a marketing strategy to create and distribute unique, interesting, understandable content to engage the audience. The reasons why a brand decides to produce content marketing is to increase brand awareness, consumer intention towards products/services, turn audiences into potential consumers, increase brand image, customer engagement, website traffic and direct sales. Digital marketing is in demand by the sports industry because fitness center, gym memberships, online fitness and fitness applications are expected to increase by 171.75% in 2028. This phenomenon is a stimulus for the sports industry sector to utilize digital marketing strategies. This is increasingly being implemented by fitness center in Bandung, because since the pandemic and the PPKM period, all activities in the fitness center have been restricted and have had an impact on a significant decrease in the number of members and turnover. This research is expected to provide information for fitness regarding purchase intention and brand engagement via Instagram to support the sustainability of their business. The research was conducted using quantitative methods on 110 respondents using a Likert scale questionnaire and analyzed using Structural Equation Modeling. The results indicated that content marketing had a 71,4% significant effect on brand engagement, and had no significant effect on purchase intention. However, brand engagement had a 73% significant effect on purchase intention and brand engagement 52,1% a mediated content marketing on purchase intention for fitness center services.